The success of the mistakes: Contributions of cognitive neuroscience in the learning process - David (Pulso. Revista de educación, 2019)
New neuroimaging techniques are allowing the exploration of the human brain's behavior at the anatomical and electromagnetic level with great precision. Since the creation of the Brain Project sponsored by Obama (2001), neuroscientific research throughout the world is providing innovative approaches with significant contributions to education. From this rises the need to readjust educational structures in order to facilitate the development of a pedagogy consistent with the new scientific evidence. Our goal is to analyze what is the predominant model to deal with mistakes in the education system in order to delineate a more efficient teaching system. For this end, we incorporate into our analysis the findings of cognitive neuroscience. Through this evaluation we establish how our learning capacities are affected by having a negative perception of mistakes. The baseline assumption is that the brain needs mistakes in order to establish an improved path for the learning process. Avoiding mistakes because they are viewed as negative, hinders our learning capacity which is necessary for the trial and error process present in all aspects of our life.